Wave Impact on a Deck or Baffle - Nor Aida Zuraimi, Md Noar; Greenhow, Martin (2015)
Some coastal or ocean structures have deck-like baffles or horizontal platforms that can be exposed to wave action in heavy seas. A similar situation may occur in partially-filled tanks with horizontal baffles that become engulfed by sloshing waves. This can result in dangerous wave impact loads (slamming) causing a rapid rise of pressures which may lead to local damaging by crack initiation and/or propagation. We consider the wave impact against the whole of underside of horizontal deck (or baffle) projecting from a seawall (or vertical tank wall), previously studied by Wood and Peregrine (1996) using a different method based on conformal mappings. The approach used is to simplify the highly time-dependent and very nonlinear problem by considering the time integral of the pressure over the duration of the impact pressure-impulse, ܲሺݔǡ ݕሻ. Our method expresses this in terms of eigenfunctions that satisfy the boundary conditions apart from that on the impact region and the matching of the two regions (under the platform and under the free surface); this results in a matrix equation to be solved numerically. As in Wood and Peregrine, we found that the pressure impulse on the deck increases when the length of deck increases, there is a strong pressure gradient beneath the deck near the seaward edge and the maximum pressure impulse occurs at the landward end of the impact zone.